"Reflecting on the Reflection…": Exploring Teacher Candidates' Assumptions of Self and Others through Facilitated Reflection. Issue 4 (1st October 2016) - Smith, Michael D.; Glenn, Tristan L.
Abstract : The literature on culturally responsive pedagogy suggests an interaction between teachers' biases and subsequent encounters with students. To gain perspective on these (un)conscious biases, teacher candidates are encouraged to (re)consider their assumptions about "the other" through reflection. This article presents findings from a study that used a two-part reflection assignment to explore teacher candidates' beliefs and predispositions about diversity, teaching, and learning. This assignment was designed as a set of companion reflection papers accessing teacher candidates' assumptions about students, families, and communities of color at the beginning and end of a diversity course. Findings from this study indicate the degree to which the "reflection-on-the-reflection" assignment (a) captures teacher candidates' initial reflections about cultural and linguistic diversity; (b) facilitates reflection on initial beliefs after exposure to diversity course content; and (c) provides instructors with data about course elements that influenced candidates' reported beliefs and assumptions .